Zooplankton Diversity and Dispersal by Birds; Insights From Different Geographical Scales - Hessen, Dag O.; Jensen, Thomas C.; Walseng, Bjørn (Frontiers in Ecology and Evolution, 2019)
Given the major ecological and evolutionary role of dispersal abilities for organisms, as well as the current interest in species’ potential for further migration and colonization as a result of climatic changes or human-mediated invasions, our knowledge about dispersal abilities on spatial and temporal scales in many taxa is surprisingly limited. Zooplankton inhabit lakes and ponds that functionally are “aquatic islands” in the landscape, and both community composition and richness depend on their ability to disperse, and their post-dispersal colonization abilities. We here assess the diversity and dispersal of freshwater microcrustaceans based on three types of data; 1) > 2000 lakes on mainland Norway spanning a wide range in longitude, latitude and altitude, 2) a more limited number of ponds at Svalbard that are differently affected by migrating birds, and 3) immigration and colonization of recently constructed wetlands and man-made ponds. At all scales we discuss whether observed patterns in diversity can be explicitly linked to birds as vectors, or if confounding factors such as climate, productivity, age of locality – or other means of immigration, precludes conclusive evidence. The spatial patterns of zooplankton distribution strongly suggest that local sorting is a major determinant of richness and community composition. This sorting may not necessarily lead to similar community composition (the “quorum effect”) however. Despite the fact that rapid colonization occurs at local scales, and that birds undoubtedly can transmit animals or resting stages, their role in modulating community structure and richness is still an unsettled issue due to the many confounding parameters. The fact that birds often play a dual role in shaping diversity and community composition, first by direct dispersal, and secondly via affecting post-dispersal species sorting by changing water quality and productivity, is an important aspect of zoochory. Direct experimental evidence (colonization with and without bird exclusion), or genetic analysis of zooplankton species along migration routes, would however be the only ways to establish firm evidence for this case of zoochory.